2013
DOI: 10.1080/10810730.2013.825664
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Patient-Centered Bilingual Prescription Drug Label

Abstract: Research shows that prescription drug labels are often difficult for patients to understand, which contributes to medication errors and nonadherence. In this study, the authors developed and qualitatively evaluated an evidence-based bilingual prescription container label designed to improve understanding. The authors developed several prototypes in English only or in English and Spanish. The labels included an image of the drug, an icon to show its purpose, and plain-language instructions presented in a 4-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…However, a number of earlier studies support the acceptability and preference of the many patient-centered modifications under study. [34][35][36] The majority of patients did not receive a benefit from the PCL, but in no instance did we find that it performed worse than standard labeling. As the intervention involved subtle modifications to pharmacy-generated labeling that could be readily put into practice, set to scale, even small increases in proper use and adherence among subgroups of consumers might yield a cost benefit.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of earlier studies support the acceptability and preference of the many patient-centered modifications under study. [34][35][36] The majority of patients did not receive a benefit from the PCL, but in no instance did we find that it performed worse than standard labeling. As the intervention involved subtle modifications to pharmacy-generated labeling that could be readily put into practice, set to scale, even small increases in proper use and adherence among subgroups of consumers might yield a cost benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, suggestions made to maintain the use of “mL” as the measurement unit and four time points to denote times for administration are consistent with those of prior studies. 19 , 35 This study has also provided a new perspective on presenting fractions, suggesting that doses should not be unnecessarily presented in multiple decimal places. Effectiveness of pictographs incorporated into written instructions to improve medication safety is supported by the existing literature; however, it is important to avoid the use of complex images.…”
Section: Discussionmentioning
confidence: 92%
“… 21 In parallel with previous findings, the participants also emphasized the need for judiciously using spacing and capitalization to improve legibility of drug labels. 21 , 33 , 34 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…[2,3] Therefore, in Malaysia, a number of public hospitals have been using the e-Hospital Information System (e-HIS) to assist in dispensing medications, with all drug-related information, including warnings and precautions, printed on a same label. [4] Although a US study also demonstrated that patients preferred having pertinent warnings and precautions presented on the main labels rather than on auxiliary labels, [5] such information could still be easily overlooked due to the lack of awareness.…”
Section: Introductionmentioning
confidence: 99%